Sammba-MRI: A Library for Processing SmAll-MaMmal BrAin MRI Data in Python - Celestine, Marina; Nadkarni, Nachiket A.; Garin, Clément M.; Bougacha, Salma; Dhenain, Marc (Frontiers in Neuroinformatics, 2020)
Small-mammal neuroimaging offers incredible opportunities to investigate structural and functional aspects of the brain. Many tools have been developed in the last decade to analyse small animal data, but current softwares are less mature than the available tools that process human brain data. The Python package Sammba-MRI (SmAll-MaMmal BrAin MRI in Python; http://sammba-mri.github.io) allows flexible and efficient use of existing methods and enables fluent scriptable analysis workflows, from raw data conversion to multimodal processing.